Conflicts Between Autonomy and Beneficence Conceptions which Affect the Therapeutics of Suicidal Attempt - Mondragón, Liliana; Monroy, Zuraya; Ito, Ma. Emily; Medina-Mora, Ma. Elena (Acta Bioethica, 2010)
The aim of this study is to know the conflicts between beneficence and autonomy principles present in physician-patientrelationship during therapy of suicidal attempt.Research was carried out in two psychiatry hospitals of the city of Mexico. The sample included three subjects with suicidal attempt,older than 18 years, attended as outpatients for an injure self inflicted last year, and three psychiatrists treating these patients.Information was obtained by individual interviews with previous informed consent. An argumentative discourse analysis was carriedout to find meaning given by participants to bioethics principles and possible conflicts between them.Conflicts between beneficence and autonomy were related to the benefit of treatment, respect to patients values and beliefs, amongothers. This study present relevant ethical considerations in the clinical scenery, by offering to the psychiatrist a bioethical analysiswhich allows him/her to act according with beneficence while respecting the autonomy of the patient in cases of suicidal attemptand, in this way, to give them better attention.